Exploring the job demands and resources of farmworkers in the South African agricultural sector - Victoria Springbok; Lene I. Graupner; Lizelle Rossouw (SA Journal of Human Resource Management, 2025)
Orientation: Farmworkers in the agricultural sector are frequently exposed to a range of occupational stressors. The interplay between job demands and available resources plays a critical role in shaping their work-related well-being.